Tariff remuneration system and methods of improvement - Portyanko, Irina; Vlasenko, Ludmila (My University, 2014)
One of the most important obligations of the employer towards its employees is their payment. Fulfilling the duties assumed, means for most employers one of the biggest expenses related to their activity. Salaries and their related costs (contributions to health, unemployment, pensions, etc.) usually add up to approximately 60% of total operating costs of a large-scale enterprise.
Keywords: оплата праці; оплата труда; wages; employer; employees; роботодавець; співробітники; работодатель; сотрудники; кафедра ділової іноземної мови та міжнародної комунікації